Measuring the Influence of the Work Environment and Innovative Behavior on Teacher Work Motivation in Public High Schools - Ashlan, Said; Fajriati, Rafni (Asian Journal of Science Education, 2024)
The purpose of this study is to ascertain and examine the effects of innovative behavior and the work environment on the motivation of teachers. Teachers at Banda Aceh City State High School served as the research participants, and a stratified proportional random sampling technique was used to create a sample size of 251 individuals. After determining the correlation between each research variable in the form of a matrix, the data were examined using route analysis. The findings indicate that innovative conduct has a positive impact on teacher work motivation of 0.309 and the work environment has a positive effect of 0.524 on teacher work motivation, according to the analysis of the influence of exogenous variables on endogenous variables in each substructure. The conclusion of the research results illustrates that there is a positive direct influence of the work environment on teacher work motivation of 22.9%, and there is a positive direct influence of innovative behavior on teacher work motivation of 17.6%. With a correlation coefficient of 0.728, the work environment and innovative conduct have an impact on teachers' job motivation at Banda Aceh City State High School concurrently. This indicates that there is a 56.4% significant effect of the work environment and inventive behavior on teacher work motivation in the adequate category. In other words, higher levels of these factors are associated with higher levels of teacher work motivation. On the other hand, teachers are less motivated to work in an environment that promotes innovation.